Soft Robotics - Design and Applications: Investigating Soft Robotics Design Principles and Applications for Developing Robots With Compliant and Flexible Structures (Journal of Computational Intelligence and Robotics, 2024)
Soft robotics is a rapidly growing field that explores the design and development of robots with compliant and flexible structures. These robots, inspired by biological systems, offer unique advantages in various applications due to their ability to interact safely with humans and delicate environments. This paper presents an overview of soft robotics design principles and highlights key applications in diverse fields such as healthcare, exploration, and manufacturing. We discuss the challenges and opportunities in soft robotics research and suggest future directions for advancing this exciting field.